Визначення концентрації діоксиду вуглецю в приміщеннях класів - Юркевич, Ю. С.; Возняк, О. Т.; Савченко, О. О.; Миронюк, Х. В.; Yurkevych, Yu.; Voznyak, O.; Savchenko, O.; Myroniuk, Kh. (Видавництво Львівської політехніки, 2018)
Дослідження стану повітряного середовища в приміщеннях класів є дуже актуальним, оскільки близько 20% загальної кількості населення проводить значну частину свого часу в дошкільних та шкільних закладах. Недотримання допустимих параметрів мікроклімату у приміщеннях класів, зокрема, внаслідок високої концент- рації СО2, призводить до погіршення самопочуття та зниження працездатності учнів, а також до недостатнього засвоєння ними навчального матеріалу. Внаслідок переви- щення допустимої концентрації СО2 у зовнішньому повітрі великих міст продуктив- ність системи вентиляції приміщень, розрахована за асиміляцією СО2, досягає значних величин. Наведено результати аналітичних досліджень зміни концентрації СО2 в приміщеннях класів протягом всього періоду перебування в них учнів при трьох схемах організації повітрообміну. Встановлено, що лише механічна припливно-витяжна вентиляція з нормою повітрообміну 30 м3/год на особу забезпечує належні санітарно- гігієнічні умови в приміщеннях класів.

In the last decade, modernization of school buildings in Ukraine is being carried out. Thermorenoval measures such as thermal insulation of exterior walls and replacement of existing windows are most often used. Installing hermetic metal-plastic windows significantly reduces the heat loss of premises, but leads to disturbance of air regime, as outdoor air infiltration is often the only source of external fresh air supply. The study of the air environment in the classrooms is very relevant, since about 20% of the total population spends a significant part of their day in preschool and school settings. Failure to comply of microclimate parameters in classrooms, in particular due to the increase of CO2 concentration, leads to deterioration of the state of health and workability of students, as well as insufficient mastering of the educational material. Due to the deterioration of the environmental state of the environment, the concentration of CO2 in the outside air of large cities often exceeds the permissible values. This leads to an increase in the productivity of ventilation systems, designed to assimilate CO2. The article presents the results of analytical studies of changes in CO2 concentration in classrooms during the entire period of their stay in the students under the three schemes of organization of air exchange, namely when closed windows during the entire training period and without ventilation; when ventilated class during each breaks and in the presence of inflow and exhaust ventilation in the classrooms. The analysis of the air environment was carried out for the most unfavorable conditions at negative external air temperatures. As a result of the research, it was established that only in the presence of mechanical inflow and exhaust ventilation with an air exchange rate of 30 m3/hour per person provides adequate sanitary and hygienic conditions in the classrooms.
Determination of carbon dioxide concentration in classes
Keywords: діоксид вуглецю; приміщення класу; повітрообмін; механічна система вентиляції; оптимальні параметри мікроклімату; carbon dioxide; classroom; air exchange; mechanical ventilation system; optimal microclimate parameters; 628.8